Thermal Self‐Protection Behavior of Energy Storage Devices Using a Thermally Responsive Smart Polymer Electrolyte. Issue 7 (17th February 2022) - Yu, Tiantian; Xue, Pan; Ma, Shaoshuai; Gu, Yifan; Wang, Yutian; Xu, Xinhua
Abstract: With the growth of high performance electronics, more consideration should be given to the safety issues associated with thermal runaway. Previous strategies have often been limited by shutdown efficiency and shutdown temperature. Here, we present a MXene supercapacitor loaded with a smart thermally responsive electrolyte to cope with thermal runaway at high temperatures. At room temperature, the ions in the electrolyte containing the poly ( N ‐isopropylacrylamide‐co‐glycidyl methacrylate) (PNGM) can migrate freely and the devices can operate normally. The smart electrolyte system forms a hydrophobic network that effectively inhibits ion migration to achieve thermal shutdown at high temperatures. The electrolyte system exhibits different electrochemical properties during heating up, reaching nearly 90 % capacity suppression at 85 °C. The proposed smart electrolyte system provides a promising solution to the thermal safety suitable for current electronic devices by achieving a proactive protection strategy. Abstract : The MXene supercapacitor loaded with smart thermal‐responsive electrolyte to cope with thermal runaway at high temperatures are provided. At low temperatures, the ions in the electrolyte containing the poly( N ‐isopropylacrylamide‐co‐glycidyl methacrylate) [P(NIPAM‐co‐GMA)] can migrate freely. Ionic migration can be suppressed with increasing temperature, even achieving over 90 % capacity suppression at 85 °C, thus preventing the device from thermal runaway. Surprisingly, the thermal‐responsive polymer can be used in common electrolytes with different pH values. The smart electrolyte system is a promising strategy.